Potential of Beef Cattle Breeding by Output Value-Based in Bayang Utara District, Pesisir Selatan Regency, West Sumatera. Issue 1 (1st February 2022) - Rastosari, Adisti; Hellyward, James; Afriani, Tinda; Rusdimansyah,; Asyraf, Mylaufa
Abstract: This study aimed to determine the potential of beef cattle breeding in Bayang Utara District, Pesisir Selatan Regency, West Sumatera. The material in this study included 135 farmers as respondents and 256 beef cattle. This research was descriptive-analytic using survey method with census data collection technique. The data obtained were analyzed descriptively. The results showed the natural increase (NI) of beef cattle as a whole was 13.28% with the NI value of each breed of beef cattle were 50.00%, 19.23%, 16.67%, 13.01%, and 9.27% for Limousin Crossbred cattle, PO cattle, Brahman Cross cattle, Simmental Crossbred cattle, and Pesisir cattle, respectively. The net replacement rate (NRR) of male and female cattle is 75.18% and 174.76%, respectively. The estimated output of beef cattle was 13.28% of the population consisting of the remaining replacement male -1.39% and female 3.88% as well as 5.6% male and 5.19% rejected cattle with the output value of each breed beef cattle were 50.00% or 1 head for Limousin Crossbred, 16.67% or 5 heads for Brahman Cross cattle, 19.23% or 5 heads for PO cattle, 13.00% or 16 heads for Simmental Crossbred and 9.27% or 7 heads for Pesisir cattle. The estimated output value of beef cattle as a whole where beef cattle can be removed was 13.28% or 34 heads. The estimated value of livestock output could be used to consider the potential development of livestock breeding in an area so that there is a sustainable breeding program.